(untitled) (Konferensiyalar | Conferences, 2024)
This article deals with the issues of bilingualism and some obstacles which can be faced by individuals in language learning and using processes. Some strategies for teaching bilingual students another foreign language are put forward. It highlights the cognitive,social, and economic features of being fluent in more than one language,as well as the difficulties that come with maintaining proficiency in multiple languages. Furthermore, the article illustrates one bilingual group students social experience in language learning journey.